Motorcycle - stopping sight distance model for geometric design of exclusive motorcycle lanes - Davoodi, Seyed Rasoul (2011)
In developing ASEAN countries, motorcycle is a popular transport mode because it is cheap and provides flexible door-to-door mobility. But motorcyclists are also highly involved in road crashes. Separating motorcycles from other vehicles in traffic by providing motorcycle lanes is a good engineering measure to improve safety of motorcyclists. In designing the motorcycle lanes, designing of geometrical elements such as the horizontal and vertical curve lengths to provide of adequate stopping sight distance at every point along the roadway are essential. There are few studies on motorcycle characteristics, but none of them addressed the safe stopping sight distance in the geometric design of motorcycle lanes.Stopping sight distance is calculated using basic principles of physics and relationships among the various design parameters. The majority parameters effects on stopping sight distance are: (i) vehicle characteristics, (ii) driver perception response time, and (iii) driver deceleration rate. This research consists of four different field studies that were undertaken under controlled testing environments for the different aspects that make up the components of the motorcycle stopping sight distance. (i) Motorcycle characteristics, which in study 1 collected real world data to construct a cumulative distribution of rider eye, motorcycle headlight, taillight and motorcyclist head heights as determined by a current motorcycle fleet in Malaysia. Characteristics of the motorcycles observed along the existing exclusive motorcycle lanes in Selangor state of Malaysia were transcribed from a camcorder, using reference dimension. (ii) Motorcyclist Braking Performance, which consisted of three different field studies to obtain riders perception response time, riders deceleration ratio (braking distance). Study 2, tested a rider’s simple perception response time. In this study participants sat on their motorcycles exactly the same way they do while riding and then they awaited activation of the taillight passenger car (parked) in front of them. Perception response times of the motorcyclists were transcribed from camcorder when the riders hit the brakes as quickly as possible following the activation of the car brake light. Study 3 and 4 evaluated rider braking performance including rider perception response time, braking performance and deceleration to an expected and unexpected object on the road. In this study 3, participants rode motorcycle and released the accelerator and applied brake as quickly as possible following activation of a light by the roadside. Study 4, measured rider braking performance when unalerted riders were confronted with the need to stop for an unexpected object that suddenly appeared in the roadway. The motorcycle characteristic study found that all 525 motorcyclist eye heights are higher than the AASHTO 2004 design value of 1,080 mm. It is noted that the 5th percentile driver eye level height is 1,350 mm while the 10th percentile motorcyclist eye level is 1,367 mm. The 5th and 10th percentile motorcycle headlight heights are 800 mm and 880 mm respectively and the 5th and 10th percentile motorcycle taillight heights are 625 mm and 634 mm respectively. The results of braking performance studies for rider simple perception response time show that the mean and the standard deviation of the motorcycle simple PRT are 0.44 sec and 0.11 sec respectively. The mean perception response time to expected and unexpected object scenario is 0.71 sec and 1.25 sec respectively. The 95th percentiles unexpected object perception response time was 2.12 sec. The findings from these studies indicated that most riders are capable of responding to an unexpected object in the roadway in 2.5 sec or less. The results of braking performance studies for rider deceleration and braking distance show that the 90 percent of all riders chose deceleration of at least 3.3 m/s2 on dry pavements. The study found that most riders chose decelerations that are greater than 2.75 m /s2. These decelerations are within riders’ capabilities to stay within their direction and maintain steering control during the braking maneuver on wet surfaces. Overall, this research proposed a motorcycle stopping sight distance model based on motorcycle characteristics, motorcyclist capabilities and performance in response to an expected and unexpected object along the exclusive motorcycle lanes. Results of this research are not only useful for eometric design of exclusive motorcycle lanes but can be used for geometric design of roads in countries with high motorcycle volumes.